Fluorescence angiography-assisted debridement of critically perfused glabrous skin in degloving foot injuries: Two case reports. Issue 22 (4th June 2021) - Vasella, Mauro; Guidi, Marco; Waldner, Matthias; Calcagni, Maurizio; Giovanoli, Pietro; Frueh, Florian S.
Abstract: Rationale: Degloving foot injuries are challenging to treat and associated with life-long sequelae for patients. An appropriate debridement of ischemic soft tissues with maximal preservation of glabrous skin is key during the reconstruction of these injuries. Indocyanine green (ICG) fluorescence angiography is an established technique for the intraoperative evaluation of tissue perfusion. Patient concerns: Two patients sustained complex foot injuries in traffic accidents, including multiple fracture dislocations and extensive degloving of the plantar skin. Diagnosis: Clinical inspection revealed significant degloving of the glabrous skin in both patients. Interventions: After fracture fixation, ICG fluorescence angiography-assisted debridement with immediate latissimus dorsi free flap reconstruction was performed. Outcomes: In both cases, this technique allowed a precise debridement with maximal preservation of the glabrous skin. The healing of the remaining glabrous skin was uneventful and the 6-month follow-up was characterized by stable soft tissues and satisfying ambulation. Lessons: ICG fluorescence angiography is a safe, user-friendly, and quick procedure with minimal risks, expanding the armamentarium of the reconstructive surgeon. It is highly useful for the debridement of extensive plantar degloving injuries and may also help to minimize the number of procedures and the risk of infection.